Breath Biomarker Analysis: The Future Point of Care Non-invasive Diagnostic Technology - Chakraborty, Surajit; Bhattacharyya, Rajasri; Banerjee, Dibyajyoti (Global Journal of Respiratory Care, 2014)
Medicine is the science and art of healing. It requires objective analysis of disease conditions to reach a meaningful conclusion. Laboratory medicine is the integral part of today’s healthcare. A classical clinical laboratory requires sample collection, sample transport, sample analysis and transfer of the report to the end user and so vital information of critical parameters are available for patient care after quite some time. Therefore, considerable current interest has been generated for non-invasive diagnostics that can be performed at the point of care. Analysis of breath biomarkers is currently understood as a topic that will be the major future point of care diagnostic methodology and this aspect is reviewed in the current manuscript to highlight the work so far done on the subject.